Antibacterial Activity of Abrus precatorius L. Leaves Against Streptococcus mutans ATCC 25175 Bacteria - Nadia Aisy Andika; Kusumaningtyas Siwi Artini; Tatiana Siska Wardani (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
One of the herbal plants that have medicinal properties is Abrus precatorius L or commonly known as Saga in Indonesia. Empirically, the boiled water of saga leaves is widely used as an ingredient in cough medicine, cancer sores and swollen tonsils. The chemical constituents of antibacterial activity in the saga leaves are glycosides (abrusoside AD and abrusgenin), flavonoids and saponins (glycerin). This study aims to determine the antibacterial activity of extracts and fractions from saga leaves and the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the most active fraction of saga leaves on the growth of Streptococcus mutans ATCC 25175. Saga leaf powder was macerated using 96% ethanol, then fractionated using n-hexane, ethyl acetate, water as solvent, 96% ethanol extract, and n-hexane fraction. The antibacterial activity test using the diffusion method showed that the extract, n-hexane fraction, ethyl acetate fraction, and water fraction of saga leaves had antibacterial activity against Streptococcus mutans. The most active fraction was the ethyl acetate fraction, with a concentration of 50% with an average inhibition zone diameter of 12.2 mm. The ethyl acetate fraction from saga leaves had the most active antibacterial activity compared to ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction, as seen from the average diameter of the inhibition zone obtained. The test results of the dilution method of the ethyl acetate fraction of saga leaves showed a Minimum Inhibitory Concentration of 12.5% and a Minimum Killing Concentration of 25%.